L’obsession médiatique de Flaubert - Alain Vaillant (Flaubert: Revue Critique et Génétique)
Of the various fixed ideas reflected in Flaubert's work, the detestation of all authoritative discourse and all asserted certainties, to which the press continually serves as an echo chamber, is the most omnipresent, to the point that one can well speak of a veritable media obsession. But this obsession reflects, more than the ironic idiosyncrasy of its author, on the one hand the real balance of power that is established between the press and literature (to the detriment of the latter), and on the other hand an ideology that is very commonly shared by writers who want to remain outside the new media culture. And this ideology is all the more vigorous because the extraordinary progress of science and technical knowledge, which has made popular books and magazines so successful, competes on another front with literary culture. Independently of what he invents in the field of writing, Flaubert is first and foremost a man of his time, whose "received ideas" he in turn reproduces.